MRI biomarkers in mild traumatic brain injury - Hähnel, Stefan; Herweh, Christian (Neurology, 2015)
In this issue of Neurology ®, Huang et al.1 describe a higher prevalence of cerebral microbleeds in patients with mild traumatic brain injury (mTBI) in comparison to healthy controls using susceptibility-weighted MRI. They could also link these observations to neuropsychological deficits as measured by the digit span score, in comparison to patients with mTBI without microbleeds.